purfavo me ajude quem é bom em monimio purfavo essa tarefa e pra manhã
a ) ab2 + ab3 + a cd - 7 a cd + a2 b+ 5 a b3
b ) 2×2 y 3 7 × 5 y
c) 7 x3 y 5. z . 7×2 . y3. z2
d) axb + 7xy z + ax2b - 7y. x z + axb - 8 a x2b
e ) 10x5 .yb .5x4 . y2 .b3
f) 25x2 y5 + 7z + 8y + 30 x2 y5 - 7z + 10z
g) x2 - [2xy +x 2 - ( y2 + 3xy ) + 2y2 ] - yy
se vc não entender a foto ok
Anexos:
Respostas
respondido por:
1
a)
ab² + ab³ + acd - 7acd + a²b + 5ab³ =
ab² + a²b + (ab³ + 5ab³) + (acd - 7acd) =
ab² + a²b + (1 + 5)ab³ + (1 - 7)acd =
ab² + a²b + 6ab³ - 6acd =
ab(b + a + 6b²) - 6acd
-------------------------------------------
b)
2x²y³7x⁵y =
(2x² . 7x⁵) (y³ . y) =
(2 . 7).(x² . x⁵) .(y³ . y) =
14 . x⁽²⁺⁵⁾ . y⁽³⁺¹⁾ =
14 . x⁷ . y⁴ =
14x⁷y⁴
-------------------------------------
c)
7x³y⁵ . z7x² . y³z² =
(7 . 7) . (x³ . x²) . (y⁵ . y³) . (z . z²) =
49 . (x⁽³⁺²⁾) . (y⁽⁵⁺³⁾ ). (z⁽¹⁺²⁾) =
49 . x⁵ . y⁸ . z³ =
49x⁵y⁸z³
---------------------------------------
d)
axb + 7xyz + ax²b - 7yxz + axb - 8ax²b =
(axb + axb) + (7xyz - 7yxz) + (ax²b - 8ax²b) =
(1 + 1)axb + (7 - 7)xyz + (1 - 8)ax²b =
2axb + 0 - 7ax²b =
2axb - 7ax²b =
axb(2 - 7x)
-----------------------------
e)
10x⁵ . yb . 5x⁴ . y² . b³ =
(10 . 5) . (x⁵ . x⁴) . (y . y²) . (b . b²) =
50 . (x⁽⁵⁺⁴⁾) . (y⁽¹⁺²⁾) . (b⁽¹⁺²⁾) =
50 . x⁹ . y³ . b³ =
50 . (x³yb)³ =
50(x³yb)³
--------------------------------
f)
25x²y⁵ + 7z + 8y + 30x²y⁵ - 7z + 10z =
(25x²y⁵ + 30x²y⁵) + (7z - 7z + 10z) + 8y =
(25 + 30)x²y⁵ + (7 - 7 + 10)z + 8y =
55x²y⁵ + 3z + 8y =
y(55x²y⁴ + 8) + 3z
----------------------------------------
g)
x² - [2xy + x² - (y² + 3xy) + 2y²] - yy =
x² - [2xy + x² - y² - 3xy + 2y²] - y² =
x² - [(2xy - 3xy) + (-y² + 2y²) + x²] - y² =
x² - [(2 - 3)xy + (-1 + 2)y² + x²] - y² =
x² - [-xy + y² + x²] - y² =
x² + xy - y² - x² - y² =
(x² - x²) + (-y² - y²) + xy =
(1 - 1)x² + (- 1 - 1)y² + xy =
0x² - 2y² + xy =
- 2y² + xy =
y(-2y + x)
ab² + ab³ + acd - 7acd + a²b + 5ab³ =
ab² + a²b + (ab³ + 5ab³) + (acd - 7acd) =
ab² + a²b + (1 + 5)ab³ + (1 - 7)acd =
ab² + a²b + 6ab³ - 6acd =
ab(b + a + 6b²) - 6acd
-------------------------------------------
b)
2x²y³7x⁵y =
(2x² . 7x⁵) (y³ . y) =
(2 . 7).(x² . x⁵) .(y³ . y) =
14 . x⁽²⁺⁵⁾ . y⁽³⁺¹⁾ =
14 . x⁷ . y⁴ =
14x⁷y⁴
-------------------------------------
c)
7x³y⁵ . z7x² . y³z² =
(7 . 7) . (x³ . x²) . (y⁵ . y³) . (z . z²) =
49 . (x⁽³⁺²⁾) . (y⁽⁵⁺³⁾ ). (z⁽¹⁺²⁾) =
49 . x⁵ . y⁸ . z³ =
49x⁵y⁸z³
---------------------------------------
d)
axb + 7xyz + ax²b - 7yxz + axb - 8ax²b =
(axb + axb) + (7xyz - 7yxz) + (ax²b - 8ax²b) =
(1 + 1)axb + (7 - 7)xyz + (1 - 8)ax²b =
2axb + 0 - 7ax²b =
2axb - 7ax²b =
axb(2 - 7x)
-----------------------------
e)
10x⁵ . yb . 5x⁴ . y² . b³ =
(10 . 5) . (x⁵ . x⁴) . (y . y²) . (b . b²) =
50 . (x⁽⁵⁺⁴⁾) . (y⁽¹⁺²⁾) . (b⁽¹⁺²⁾) =
50 . x⁹ . y³ . b³ =
50 . (x³yb)³ =
50(x³yb)³
--------------------------------
f)
25x²y⁵ + 7z + 8y + 30x²y⁵ - 7z + 10z =
(25x²y⁵ + 30x²y⁵) + (7z - 7z + 10z) + 8y =
(25 + 30)x²y⁵ + (7 - 7 + 10)z + 8y =
55x²y⁵ + 3z + 8y =
y(55x²y⁴ + 8) + 3z
----------------------------------------
g)
x² - [2xy + x² - (y² + 3xy) + 2y²] - yy =
x² - [2xy + x² - y² - 3xy + 2y²] - y² =
x² - [(2xy - 3xy) + (-y² + 2y²) + x²] - y² =
x² - [(2 - 3)xy + (-1 + 2)y² + x²] - y² =
x² - [-xy + y² + x²] - y² =
x² + xy - y² - x² - y² =
(x² - x²) + (-y² - y²) + xy =
(1 - 1)x² + (- 1 - 1)y² + xy =
0x² - 2y² + xy =
- 2y² + xy =
y(-2y + x)
iingryd45gmailcom:
obrigado mesmo
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás